Book review - Kaijanangoma, Dietrick K (University of Dar es Salaam Library Journal, 2020)
Fundamentals of Communication Research in Africa: A Contemporary View engages with the complex and dynamic landscape in contemporary Africa by exploring the various relationships between foundations of research, its essentials, processes, and guidelines on writing techniques